A strategy to maintain the organoleptic quality of flavor-β-cyclodextrin inclusion complexes: Characteristics aroma reconstruction of Osmanthus absolute. (15th February 2023) - Shi, Qingzhao; Chai, Guobi; Xu, Xiujuan; Fan, Wu; Wu, Chaojun; Ji, Lingbo; Xi, Hui; Mao, Jian; Liu, Junhui; Song, Yubing; Zhang, Qidong
Abstract: The proportion of odorants has a key effect on the odor/flavor profile of perfumes or food products. However, direct encapsulation changes the odorant release characteristics, resulting in corresponding variations in their organoleptic qualities. In this study, nine key odorants (KOs) of Osmanthus absolute (OA) were identified for the aroma reconstruction of OA. Inclusion complexes of β-cyclodextrin (β-CD) with KOs (KO-β-CDs) were obtained via co-precipitation, the loading of KOs in β-CD was varied from 34.86 to 108.88 mg/g. Based on the aroma release behavior analyses, main aroma characteristics of OA were reconstructed from the KO-β-CDs via replication of the headspace KO distributions of OA. Aroma profile evaluation validated the effectiveness of aroma reconstruction. Besides, the release characteristics of directly encapsulated OA (OA-β-CD) and OA were found to significantly differ. For example, linalool oxide furanoid contributed greater than 20% of the total KOs in the headspace of OA, contributed only 8.89% in the headspace of the OA-β-CD. Further, the aroma intensity of the five main descriptors was reduced to different degrees. The KO-β-CDs mixture resembles the odor profile of OA to a greater degree than OA-β-CD. Our methodology provides a route to maintain the organoleptic quality of flavors in β-CD inclusion complexes. Graphical abstract: Image 1 Highlights: Organoleptic quality of OA was changed after being encapsulated with β-cyclodextrin. Main aroma characteristic of OA was reconstructed using a mixture of the KO-β-CDs. The mixture bears a strong aromatic resemblance to OA.